What Makes Customers Intend to Reuse Online Transportation Service? Evidence from West Java, Indonesia - Wahyudayanto Utama; Elvira Azis; Erni Martini (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effect of service quality, word of mouth, and customer satisfaction on reuse intention among Gojek users. Service quality is reflected by four dimensions: tangibles, responsiveness, reliability, and assurance. Data were analyzed using partial least squares structural equation modeling (PLS-SEM) with 346 respondents from West Java, Indonesia, all of whom actively use the Gojek application. The results show that service quality, customer satisfaction, and word of mouth all directly and significantly influence reuse intention, with word of mouth exerting the strongest effect. Service quality also indirectly influences reuse intention through customer satisfaction and word of mouth. Keywords: Reuse Intention; Customer Satisfaction; Service Quality; Word of Mouth